The Laser Inventor Memoirs of Theodore H. Maiman - Maiman, Theodore H. (Springer Biographies, 2018)
In these engaging memoirs of a maverick, Theodore H. Maiman describes the life events leading to his invention of the laser in 1960. Maiman succeeded using his expertise in physics and engineering along with an ingenious and elegant design not anticipated by others. His pink ruby laser produced mankind's first-ever coherent light and has provided transformational technology for commerce, industry, telecom, the Internet, medicine, and all the sciences. Maiman also chronicles the resistance from his employer and the ongoing intrigue by competing researchers in industry and academia seeking to diminish his contribution in inventing the first laser. This work will appeal to a wide readership, from physicists and engineers through science enthusiasts to general readers. The volume includes extensive photos and documentary materials related to Maiman's life and accomplishments never before published. "No one beat Maiman to the laser. How important is the laser? How important are all lasers? That is how important we have to regard Maiman's contribution.He and the laser changed all of our lives, everyone's!" Dr. Nick Holonyak, Jr., Professor of Electrical and Computer Engineering and Physics, University of Illinois at Champaigne-Urbana, and inventor of the light-emitting diode (LED) and co-inventor of the transistor laser "More than five decades later, we can safely conclude that Theodore Maiman's groundbreaking discovery changed the world. Our modern life just as scientific research would be quite different without the laser." Dr. Ferenc Krausz, Director, Max Planck Institute for Quantum Optics, Garching, Germany, and Professor of Physics, Ludwig Maximilian University, Munich, and pioneer in attosecond lasers and attophysics "Maiman had the stroke of genius needed to take a different approach [from his competitors]. The sheer elegance and simplicity of his design belies the intellectual achievement it represents. If his invention seems obvious to some today, it was far from obvious in 1960." Jeff Hecht, authoritative science writer on the historical development of the laser, author of books on lasers and fiber optics.